The Temporal and Spatial Epidemiology Employed in the Elimination of the HIV Epidemic in the Largest Capital of the Brazilian Rainforest - Bruna Rafaela Leite Dias; Taymara Barbosa Rodrigues; Dulce Gomes; Ricardo Alexandre Arcêncio; Elucir Gir; Glenda Roberta Oliveira Naiff Ferreira; Sandra Helena Isse Polaro; Eliã Pinheiro Botelho (Tropical Medicine and Infectious Disease, 2022)
Background: The main goal of this study was to analyze the human immunodeficiency virus (HIV) epidemic temporally and spatially in Belém from 2007 to 2018. Methods: The incidence rates were analyzed according to time using autoregressive integrated moving-average models, as well as spatially using spatial autocorrelation, Kernel density, scan statistics, and regression techniques. Results: During the study period, 6007 notifications of new cases of HIV/AIDS were reported. The time series analysis revealed a stabilized trend of incidence from 2007 to October 2016, followed by irregular fluctuations until the end of December 2018. Seasonal behavior was observed from 2019 to 2022. The high–high incidence clusters were found in the central and transition areas. An expansion of the number of new reported cases was observed in the central area. Three spatial risk zones were observed. The higher relative risk zone was concentrated in the transition area. The spatial regression showed that the incidence rates were positively correlated with the Family Health Strategy (FHS) coverage. Conclusions: To eliminate HIV in Belém, it will be necessary to decentralize testing and ART and expand the coverage of FHS to ensure universal access to healthcare for citizens.